2015
DOI: 10.14808/sci.plena.2015.094501
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a UV-VIS Spectrophotometric method for the determination of usnic acid /collagen-based membranes

Abstract: O ácido úsnico (AU) é um metabólito secundário de líquens que tem demonstrado potenciais efeitos farmacológicos, tais como atividade antimicrobiana, antiviral, antiproliferativa e anti-inflamatória. O colágeno, por sua vez, é um dos biomateriais mais utilizados visando o desenvolvimento de sistema de liberação de fármacos. Sendo assim, o objetivo deste estudo foi desenvolver e validar um método analítico por espectrofotometria na região do ultravioleta (UV) para determinação de concentrações de AU em membranas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Nickel production. Any p-value less than 0.05 in ANOVA testing shows a significant difference between two treatments (Nunes et al, 2015). The large p-values for all three combinations in Figure 6 indicate that there were not any notable changes in usnic acid production within the metal-free, low nickel, and high nickel treatment groups.…”
Section: Standard Curvementioning
confidence: 88%
See 3 more Smart Citations
“…Nickel production. Any p-value less than 0.05 in ANOVA testing shows a significant difference between two treatments (Nunes et al, 2015). The large p-values for all three combinations in Figure 6 indicate that there were not any notable changes in usnic acid production within the metal-free, low nickel, and high nickel treatment groups.…”
Section: Standard Curvementioning
confidence: 88%
“…Previous studies on usnic acid synthesis in lichens have identified several of the chemical reactions needed to make this molecule, but certain steps in the metabolic pathway remain unknown (Nunes et al, 2015). As a result, the majority of usnic acid's properties cannot be predicted, and they are generally discovered through sampling or experimental designs instead.…”
Section: Properties Of Usnic Acidmentioning
confidence: 99%
See 2 more Smart Citations
“…ANOVA test (one-way) was performed based on the absorbance values observed for each ascorbic acid concentration during the replicate measurement of the standard solutions. The linearity of the calibration process was investigated by means of the Lack-offit test (Akritas and Papadatos, 2004;de Souza and Junqueira, 2005;Hsieh and Liu, 2008), the quality coefficient (De Beer et al, 2007;Tellinghuisen, 2008), correlation coefficient (Van Loco et al, 2002;de Souza and Junqueira, 2005;Asuero et al, 2006;Hsieh and Liu, 2008), determination coefficient (Van Loco et al, 2002), ANOVA (Nunes et al, 2015;de Haro Moreno et al, 2018).…”
Section: Linearitymentioning
confidence: 99%